Experimental study on concrete columns reinforced by hybrid steel-fiber reinforced polymer (FRP) bars under horizontal cyclic loading. (15th January 2017) - Sun, Zeyang; Wu, Gang; Zhang, Jian; Zeng, Yihua; Xiao, Wenchao
Highlights: We tested four concrete columns under cyclic loading. The reinforcements including steel bars, hybrid steel/FRP bars, and SFCBs. The failure modes and hysteretic behaviors were analyzed. Abstract: Effective post-yield stiffness of reinforced concrete (RC) columns can significantly contribute to the seismic performance of RC structures. However, because of the elastoplastic properties of steel bars, the post-yield stiffness of an ordinary RC column can be very slight or even negative. Fiber reinforced polymer (FRP) can provide a high degree of ultimate strength, light weight, and protection from corrosion. By combining steel and FRP, a designable post-yield stiffness can be achieved for concrete structures reinforced with steel-FRP composite bars (SFCBs) or hybrid steel/FRP bars. This paper conducted cyclic loading tests on four concrete columns with different reinforcement types, including steel bars, hybrid steel/FRP bars, and SFCBs. The test results showed that (1) the columns reinforced with different bars had similar strain distributions from column base to cap prior to yielding. After yielding, the plastic deformation of the ordinary RC column concentrated at the column base and the loading capacity decreased with the increase of lateral drift because of the P - δ effect. (2) Unlike the negative post-yield stiffness of an ordinary RC column, the post-yield stiffness of a column with hybrid reinforcements was positive. As the post-yield stiffness ratio of the longitudinal reinforcement increased by 27 percent, the post-yield stiffness of the concrete column increased by 7.4 percent. Therefore, the corresponding displacement ductility could reach 11—much greater than that of the RC column (6.28). (3) As a result of the more robust hysteretic curve of the RC column, the equivalent viscous damping coefficients of the RC column were greater than those of the hybrid column, whereas the hybrid reinforced concrete columns could dissipate earthquake energy without a corresponding loss of strength.